Website Quality Analysis Using Customer Satisfaction Index and Importance Performance Analysis - Lady Hasiani Siahaan; Gusti Made Arya Sasmita; Gusti Agung Ayu Putri (CESS (Journal of Computer Engineering, System and Science), 2022)
The development of technology in the digital era is currently growing very rapidly it is including in education, such as the creation of an academic information system that aims to facilitate the process of the needs of lecturers, employees and students in terms of document management and other academic needs. Website quality analysis used Service quality is measured using the Customer Satisfaction Index with the SIMAK-NG service and the Importance Performance Analysis method to analyze the quality of SIMAK-NG service performance. The results of the analysis satisfaction of lecturers and employees of website users on the SIMAK-NG website were "VERY SATISFIED" with a percentage rate of 82.03% but there was still a GAP value between website performance and user expectations. In the IPA quadrant, the main improvement priorities were 3 items of questions for lecturers and employees and 10 items that become website achievements.